kesadaran ibu hamil terhadap tanda bahaya kehamilan - Siti Mawaddati Mazirah; Dian Roza Adila; Raja Fitrina Lestari (Jurnal Ilmu Keperawatan, 2022)
Pregnancy starts from the formation of gametes to implantation in the uterus. Pregnancy is a normal phenomen on that can be accompanied by danger signs of pregnancy that can cause complications. This danger sign of pregnancy can occur in the first trimester to the third trimester. Pregnant women need to recognize potential problems and risks that can occur by having awareness about their health, so they can make quick and appropriate decisions in seeking health services. This study aims to determine the description of pregnant women's awareness of the danger signs of pregnancy. This type of research is quantitative with a descriptive design using univariate analysis on age, education, gravida, ANC visits, and awareness of pregnancy danger signs presented in the form of frequency distribution. The sample of this study were 80 pregnant women with accidental sampling technique at Simpang Tiga Health Center which were taken by questionnaire. The results of the analysis showed that the majority of mothers were not at risk (77.5%), high school education (52.5%), multigravida (56.3%), ANC visits >4 times (61.3%). The majority of mothers have poor awareness of the danger signs of pregnancy based on age, education, gravida, and ANC visits. The majority of mothers were aware of bleeding (87.5%) as a danger sign of pregnancy, and the majority of mothers were not aware of swelling of their hands and face (70.0%) as a danger sign of pregnancy. The results of this study were the awareness of pregnant women to the danger signs of pregnancy was still poor (45.0%). It is hoped that mothers will have more awareness of the danger signs of pregnancy by conducting regular ANC visits to obtain information and mothers to open and read MCH books if problems occur in pregnancy, so that mothers can make decisions to immediately seek health services.